THE ROLE OF CIVIC EDUCATION IN FOSTERING CIVIC RESPONSIBILITY - Aenul Hayati, Auliya; Pratiwi Dwi Santi, Dina; Rahma Indah, Ade; Sariani, Sherina; Fasya Maulani, Monica (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research highlights the urgency of Civic Education in shaping an integrity-driven and socially contributing generation. Systematically, the study reviewed literature on the role of Civic Education in fostering civic responsibility. The analysis focused on relevant journals published between 2016 and 2024 in the SINTA database. Findings indicate that Civic Education plays a crucial role in shaping positive citizenship values and character. Publication trends peaked between 2019 and 2022, consistently covering topics such as affective assessment, anti-corruption education, the role of local wisdom, extracurricular programs, and various learning approaches like CTL and discovery learning. Qualitative research predominates, including Classroom Action Research, Research and Development, Quasi Experiment, Observational Studies, Mixed Designs, Survey Research, and Ex Post Facto Design. Qualitative descriptive analysis is preferred over t-tests and Analysis of Variance. Observation, interviews, and documentation are the most commonly used instruments, primarily found in SINTA 4 journals. Sequentially, the primary research subjects include Primary School Teacher Education (PGSD) students, Upper Primary School students, Grade X High School students, Lower Primary School students, Grade XI High School students, and Civic Education undergraduate students. Recommendations for sustainable research emphasize the urgency of effective holistic approaches and strategies in instilling citizenship values to develop students' roles and responsibilities as young citizens, suitable for publication in international-scale journals.